Efficacy and Safety of Intranasal Esketamine in Patients With Treatment-Resistant Depression and Comorbid Chronic Post-traumatic Stress Disorder: Open-Label Single-Arm Pilot Study - Rothärmel, Maud; Benosman, Cherifa; El-Hage, Wissam; Berjamin, Caroline; Ribayrol, Diane; Guillin, Olivier; Gaillard, Raphaël; Berkovitch, Lucie; Moulier, Virginie (Frontiers in Psychiatry, 2022)
Introduction: Major depressive disorder is more likely to resist to usual treatment when it is associated with post-traumatic stress disorder (PTSD). Capitalizing on the effect of ketamine in both treatment-resistant depression (TRD) and PTSD, we conducted a study in order to assess the efficacy of intranasal (IN) Esketamine in patients having TRD with comorbid PTSD. Methods: In this open-label, single arm, retrospective pilot study,11 patients were treated with IN Esketamine (56 or 84 mg) with a longitudinal follow-up of 6 months. IN Esketamine was administered twice weekly during the first month, once weekly during the second month, and then once every one or two weeks. Patients were assessed with Montgomery-Åsberg Depression Rating Scale (MADRS), Patient Health Questionnaire 9 items, Global Assessment of Functioning and Clinical Global Impression-Suicide Scale. Results: We included 9 women and 2 men (mean age 47.3 ± 11.1 years). The mean (SD) MADRS scores decreased significantly from 38.6 (6.4) at baseline to 18.2 (10.03) after 6 months of IN Esketamine; 7 patients were responders and 3 patients were in remission. The percentage of patients who were moderately to severely suicidal declined from 63.6% at baseline to 27.3% after 1 month of IN Esketamine sessions. No serious adverse reactions were observed. Conclusion: This study reports the outcomes of 11 severely ill patients with comorbid TRD and PTSD after IN Esketamine treatment. Esketamine significantly improved depression symptoms, suggesting that it is likely to be a treatment of choice in this specific population.